A Weed in the Church: Early 20th Century American Historical Perspectives on Adolescence and the Rise of Modern Youth Ministry - Droege, Michael W. (Journal of youth and theology, 2025)
This research pulls from a historical and theoretical lens to suggest that a misapplication of adolescent theory flowing from the moral panic of the 20th century has been realized in the exclusion of adolescence from ecclesial participation, resulting in generational disengagement with the institutional church. The path forward includes a consideration of how identity is formed within communities in an ecosystem of reciprocity that takes seriously the contribution of each generational cohort. While particular attention is given to both the historical praxis of youth ministry as well as the theological implications of youth ministry, this research is intended to invite further consideration of the subject of adolescent formation from a developmental, historical, and theological viewpoint.